2019
DOI: 10.1039/c9sc03521d
|View full text |Cite
|
Sign up to set email alerts
|

A lipidomic workflow capable of resolving sn- and CC location isomers of phosphatidylcholines

Abstract: Large-scale profiling of phosphatidylcholines at the isomer level is achieved by incorporating gas-phase radical-directed fragmentation into an LC-MS/MS workflow.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
77
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 67 publications
(82 citation statements)
references
References 48 publications
4
77
1
Order By: Relevance
“…In addition to the C=C locations, sn -positions of PCs in single cells could also be identified. It has been reported that the sn -position of PCs could be identified by negative mode MS/MS analysis with the adduct of bicarbonate anion (HCO 3 − ) 25 . This method was adapted in this study for the single-cell lipid analysis by changing the assisted solvent to 50 mM ammonium bicarbonate solvent in methanol:acetonitrile:water = 4.5:4.5:1 (v/v).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to the C=C locations, sn -positions of PCs in single cells could also be identified. It has been reported that the sn -position of PCs could be identified by negative mode MS/MS analysis with the adduct of bicarbonate anion (HCO 3 − ) 25 . This method was adapted in this study for the single-cell lipid analysis by changing the assisted solvent to 50 mM ammonium bicarbonate solvent in methanol:acetonitrile:water = 4.5:4.5:1 (v/v).…”
Section: Resultsmentioning
confidence: 99%
“…The chemical structures of lipids are very complex and a significant amount of efforts have been put in the discovery of interesting chemistry (e.g., photochemical reactions and epoxidation) for elucidating lipid structures using MS 21 . Paternò-Büchi (PB) reaction combined with tandem MS is one of the most effective protocols for the detailed characterization and relative quantitation of lipids at carbon-carbon double bond (C=C) location and sn-position levels [22][23][24][25][26] . Epoxidation is also common in deep lipidomic analysis with C=C location specificity, owing to its universal accessibility [27][28][29][30][31] .…”
mentioning
confidence: 99%
“…PB reaction converts the C=C to an oxetane which can be preferentially fragmented by low-energy collisioninduced dissociation (CID). Other approaches include ion mobility spectrometry (IMS) 36,37 and alternative gas-phase ion activation [38][39][40][41][42][43][44] . These lipid characterizing methods were also compatible with mass spectrometry imaging (MSI) [45][46][47][48][49][50] .…”
mentioning
confidence: 99%
“…For instance, studies suggested positive associations between high ratios of dietary ω‐6:ω‐3 PUFAs and production of inflammatory mediators, while increased consumption of ω‐3 PUFAs appeared to suppress inflammation 6,7 . Moreover, changes in C18 (∆9):(∆11) were observed in breast cancer 8–10 . Mass spectrometry (MS) is a primary tool for lipid structure characterization.…”
Section: Introductionmentioning
confidence: 99%